Sero-prevalence and PCR identification of lumpy skin disease virus in cattle at Mymensingh district of Bangladesh - Saad Muhammad Rafe-Ush-Shan; Ruhena Begum; Milton Roy; Muhammad Mujahidul Islam; Hemayet Hossain; Md. Shahidur Rahman Chowdhury; Md. Bashir Uddin; Md. Mahfujur Rahman; Md. Mukter Hossain (Veterinary Integrative Sciences)
Lumpy skin disease (LSD) is a transboundary, an infectious viral disease of cattle causing substantial economic losses due to skin damage and decreased animal production. This study aimed to determine the serological prevalence and molecular detection of lumpy skin disease virus (LSDV) from cattle in Mymensingh district, Bangladesh with assessment of risk factors. A total of 200 samples consists of whole blood (184), tissue (10) and pus (6) were collected from three different Upazilas of Mymensingh and tested using indirect enzyme linked immunosorbent assay (ELISA) kit. The DNA was extracted from whole blood using a DNA extraction kit and kept at -20°C until further analysis. Extracted DNA was used in a PCR test to detect lumpy skin disease virus (LSDV). Overall, the sero-prevalence of LSD among cattle in Mymensingh was 28.26% (52/184) (CI: 19.36-38.61). Fulbaria Upazilas showed the highest prevalence of 30% (24/80) compared to Mymensingh Sadar 24% (12/50) and Muktagacha 29.63% (16/54). Moreover, the risk of getting LSD infection was lower among cross breed (OR=0.27, CI: -0.1-0.75) and female animals (OR=0.39, CI: -0.15-1.03). Furthermore, freely grazing animal 29.17% (CI: 12.61-51.09) and young group 72.73% (CI: 39.03-93.98) of animal showed risk in having lumpy skin disease. LSD virus was detected in the sero-positive blood sample (100%), tissue sample (90%), and pus/edema fluid discovered (83.33%) after amplification of a 192 bp DNA fragment. The findings of this study will be helpful in creating efficient methods for identifying and managing LSD in Bangladesh and avoiding the financial losses connected with dairy production.